PROSEDUR PEMOTONGAN PAJAK PERTAMBAHAN NILAI TERHADAP ALOKASI DANA DESA DI DESA BELLU KECAMATAN SALOMEKKO KABUPATEN BONE - Haeruddin Haeruddin (AkMen JURNAL ILMIAH, 2018)
This research aims to know the procedure of tax deduction of value added to the allocation of village funds, This research using descriptive method with qualitative approach. The type of data was primary data and secondary data.Data collection was done by interview and documentation. Analisys data method used was descriptive qualitative. The results of this reserch indicated that the partners submit tax invoices or bills to the village treasurer over the submission of BKP or JKP. The payment made by the village treasurer to the counterparty for invoices based on the tax invoice was the payment after the VAT deducted, after tax consultant deposits the VAT then the E-Billing evidence is than handed back to the village treasure to be archived and submitted to partners.